Nekrolog over Henning Høirup - Pedersen, Kim Arne (Grundtvig-studier, 1996)
Henning Høirup in memorian By Kim Arne Pedersen Only two years before the fiftieth anniversary of the Grundtvig Society, it suffered the loss of one of its founders and pioneers, Bishop and Doctor of Divinity Henning Høirup. The present obituary begins with a recapitulation of Høirup’s own account, in articles and in his memoirs, of the foundation of the Grundtvig Society and the circumstances behind its formation. The Grundtvig Society has its background in the Danish Grundtvig Renaissance during World War II, both its popular and existential and its more academic side. Among the inspirations behind it were the Grundtvigian »self-reflection movement« around the Independent Church clergyman Anders Nørgaard and the Tidehverv Grundtvigianism which is inspired by dialectic theology in its interpretation of Grundtvig. At the same time it was a decisive consequence of the formation of the Grundtvig Society that there was a new vivid interest in Grundtvig’s writings in circles that had not hitherto occupied themselves with them.Høirup combined the existential and the academic approach to Grundtvig’s universe. It was highly approved of by Høirup that Grundtvig became accessible to circles outside the Grundtvigian movement. Høirup came from a Grundtvigian background himself, but was never a strict partisan, even though he was in touch with the two Grundtvigian movements mentioned above and was rooted in the .neo-Grundtvigian. movement through his family.Høirup’s childhood home shared the profound interest taken by this movement in social and political issues, but combined it with a broad cultural outlook which, more than anything else, was Høirup’s inheritance from his childhood home. In his high school years Høirup took a vivid interest in literature, art and history, but nevertheless chose to become a student of theology. During his studies he experienced a growing involvement in theological issues, inspired by Karl Barth’s theology, but was also deeply influenced by his teachers. Thus, the church historian, Professor Jens N.rregaard’s influence is reflected in Høirup’s interest in ecclesiology, and that of the systematic theologian, Professor Eduard Geismar, in his emphasis on existential life conditions as the point of departure of theology.Høirup was the first scholar in Denmark to write a doctoral thesis on Grundtvig. The thesis, which is the fruit of Høirup’s broad theological and humanistic learning, begins with an account of Grundtvig’s theory of cognition in the light of history of philosophy. According to Høirup, this theory is founded partly on the emphasis, in pre-Kantian Rationalism, of the contradictory principle as a fundamental ontological .law., partly on English Empiricism, used by Grundtvig in connection with history. To Grundtvig, the maxim of contradiction becomes an expression of the contradictory relationship between life and death which is manifested in the renunciation of the Confession of Faith. Thus, the maxim of contradiction is behind the emphasis, inherent in the Grundtvigian view of the church, on the community of the congregation as the life condition where man meets the word of the living God. Despite its basic character as church history, the thesis, then, aims at a dogmatic analysis of Grundtvig’s church view.Høirup carried out his scholarly research, first while working as a vicar on Funen, later as a dean in Viborg, and finally, in the period from 1963 to 1979, as the Bishop of the Diocese of .rhus. The demanding offices gave Høirup a number of very busy years. All the same, he produced a series of eminent studies in Danish culture and literature and, above all, in the writings and impact of Grundtvig. Among them should be mentioned the book Fra D.den til Livet (From Death to Life) from 1954, the book about Frederik Lange Grundtvig from 1955, and the study of Grundtvig and Ansgarius from 1965-1966 (Danish and German editions). In addition a large number of articles appeared, among them the study of Grundtvig’s and Kierkegaard’s church view, published in English in an American theological periodical. His activities also comprised editorial work, for example Grundtvigs Erindringer og Erindringer om Grundtvig (Grundtvig’s Memoirs and Memories of Grundtvig), in collaboration with Steen Johansen, 1948, and he also found time to participate in and supervise the registration of Grundtvig’s unprinted papers.Having been the editor of the first volumes of Grundtvig Studies during the period 1948 to 1953, Høirup became the chairman of the Grundtvig Society at Scharling’s death in 1951, a post he filled until 1972. In recent years Høirup followed the activities of the Soicety with great interest, and just before he died he was doing research into Grundtvig’s family and Grundtvig’s relationship with his mother.